Updating State and Local Highway Cost Allocation and Revenue Attribution: A Case Study for Indiana. Issue 1 (2016) - Agbelie, Bismark R. D. K.; Volovski, Matthew; Zhang, Zhibo; Bardaka, Eleni; Labi, Samuel; Sinha, Kumares C.
This study investigated the responsibility for the cost of upkeep of the highway infrastructure and the contribution of revenue from highway users on that upkeep. The costs consisted of actual expenditures on the construction, preservation, maintenance, and operation of the infrastructure at both the state and the local levels. The revenues from the federal, state, and local levels were assessed and considered. The types of assets included were pavement, bridge, safety, and mobility assets. The highway users were represented by the 13 FHWA vehicle classes, and the study was based on data on the expenditures made and the revenues collected from 2009 to 2012. The study framework duly recognized the dichotomy between attributable and common costs: for allocation of the attributable costs to the vehicle classes, equivalent single-axle loads, AASHTO load equivalency factors, and passenger car equivalents were used, and for allocation of common costs, the number of vehicle miles traveled adjusted for vehicle width was used. Of the 13 vehicle classes, Vehicle Classes 1 to 4 (passenger vehicles) were found to be overpaying their cost responsibilities, whereas Vehicle Classes 5 to 13 (trucks) were found to be underpaying. In particular, Vehicle Class 2 (automobiles) was found to overpay its cost responsibility by 10%, whereas Vehicle Class 9 (five-axle trucks) was found to underpay by 19%. The product of this study facilitates assessment of the appropriateness of the types and rates of current taxes and fees and provides a data-based and objective platform for devising future funding mechanisms and establishing appropriate user rates to meet Indiana's future financing needs.